Humans and the environment in northern Baikal Siberia during the Late Pleistocene - Chlachula, Jiří (Geologos, 2019)
Book review: Humans and the environment in northern Baikal Siberia during the Late Pleistocene, by E.M. Ineshin and A.V. Teten’kin (translated by P.N. Hommel and N. Reynolds), Cam-bridge Scholars Publishing, Newcastle upon Tyne, UK. 337 pages. Hardback: price £64.99. ISBN (10): 1-4438-8277-1; ISBN (13): 978-1-4438-8277-4.